2022
DOI: 10.1108/jtf-07-2021-0180
|View full text |Cite
|
Sign up to set email alerts
|

Scenarios for New Zealand tourism: a COVID-19 response

Abstract: PurposeA case study about the creation of four scenarios that were used to make sense of the fast-moving pace of COVID-19 and the consequences for New Zealand tourism.Design/methodology/approachAdapting global visitor economy scenarios, a set of New Zealand tourism scenarios were constructed using a “back of house Shell” method and were supplemented with an expert panel to test the reliability and validity of the scenarios.FindingsThe four scenarios constructed were based on two critical uncertainties, namely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…If something has indeed been learned over the last two years of the pandemic, an increased concern for sustainability issues and responsible tourism models is quite likely (Postma and Yeoman, 2021). In this sense, and taking into account the four post-COVID-19 scenarios for global tourism in 2025 that Yeoman et al (2022) outlined, let us hope that will come true the scenario of "responsible tourism", characterised by "A rethinking of the relationship of tourism with the ecosystem; a sustainable and balanced future; a conscious, well-informed and responsible holiday behaviour; rethinking capitalism" (Yeoman et al, 2022, p. 186).…”
Section: A Paradigmatic Tourism Scenario Of Sars-cov-2 Global Dissemi...mentioning
confidence: 99%
See 1 more Smart Citation
“…If something has indeed been learned over the last two years of the pandemic, an increased concern for sustainability issues and responsible tourism models is quite likely (Postma and Yeoman, 2021). In this sense, and taking into account the four post-COVID-19 scenarios for global tourism in 2025 that Yeoman et al (2022) outlined, let us hope that will come true the scenario of "responsible tourism", characterised by "A rethinking of the relationship of tourism with the ecosystem; a sustainable and balanced future; a conscious, well-informed and responsible holiday behaviour; rethinking capitalism" (Yeoman et al, 2022, p. 186).…”
Section: A Paradigmatic Tourism Scenario Of Sars-cov-2 Global Dissemi...mentioning
confidence: 99%
“…It could have been expected that the COVID-19 pandemic might have constituted a decisive tipping point for a deprioritising of the economy, considering the tourism system as a means to serve society and the sustainable development goals (SDGs) that foresee the viability of our common future (G€ ossling et al, 2021;Higgins-Desbiolles, 2018). However, instead of considering the current crisis of the pandemic, together with the climate crisis, as imperative reasons for urgent structural changes in global mass tourism (Jamal and Budke, 2020), it is quite likelyamong other possible scenarios of "survival of the fittest" (collapse), "business as unusual" (transition) and "responsible tourism" (transformation) (Postma et al, 2020;Yeoman et al, 2022) that there will be a return to "business as usual" (growth) and the old normality of unsustainable tourism as soon as the health crisis is overcome (Hall et al, 2020;Ioannides and Gyim othy, 2020;V arzaru et al, 2021). In fact, the dominant concern has been the profound negative economic impact of COVID-19, especially in regard to tourism (Sharma and Nicolau, 2020;U gur and Akbıyık, 2020;United Nations, 2020;Yeh, 2021), with a constant reiteration of the urgency of resuming stimulating activity, based on a "boosterist", expansionary and pro-growth motivation (Higgins-Desbiolles, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As futures studies is grounded in Dator's Law (Dator, 2019) in which the future cannot be predicted but alternative futures can be forecasted, the concept of plurality is at the centre of futures studies, and scenario planning is the main methodology to envision the future (Amer et al, 2013;Yeoman and McMahon-Beattie, 2014). Using these principles, Yeoman et al (2022c) created four scenarios that were used to make sense of the fast-moving pace of COVID-19 and the consequences for New Zealand tourism. The four scenarios constructed were based on two critical uncertainties, namely economic recession and the moral dilemma of the consumer.…”
Section: Covid-19 Arrives: Which Direction?mentioning
confidence: 99%
“…Using a foresight framework, the research identifies and challenges assumptions about how a current situation may evolve in the future. The authors highlight how scenarios are an important instrument in resilience building at macro and meso levels, concluding the concept of plurality in using scenarios (Yeoman et al, 2021(Yeoman et al, , 2022. Applying this concept of plurality, Becken and Loehr (2023) (2023) writes, during the pandemic, two types of fear were identified that occur significantly in all groups or profiles of people.…”
mentioning
confidence: 99%
“…Using a foresight framework, the research identifies and challenges assumptions about how a current situation may evolve in the future. The authors highlight how scenarios are an important instrument in resilience building at macro and meso levels, concluding the concept of plurality in using scenarios (Yeoman et al , 2021, 2022). Applying this concept of plurality, Becken and Loehr (2023) provide a range of narratives of what the future of the Asia Pacific tourism may look like beyond COVID-19 and identifying how current tourism policy interventions will shape the future, along with future responds.…”
mentioning
confidence: 99%